In vitro models of medulloblastoma: choosing the right tool for the job - Ivanov, Delyan P.; Coyle, Beth; Walker, David A.; Grabowska, Anna M. (Elsevier, 2016)
The recently-defined four molecular subgroups of medulloblastoma have required updating of our understanding of in vitro models to include molecular classification and risk stratification features from clinical practice. This review seeks to build a more comprehensive picture of the in vitro systems available for modelling medulloblastoma.